Career development, compensation, job security, workplace environment and employee loyalty in Universiti Putra Malaysia (UPM) / Muhammad Ameer Shafiq Awang@Ali - Awang @ Ali, Muhammad Ameer Shafiq (2019)
The purpose of the study is to know whether there is a relationship between each variable and to find the most contributes that influence employee loyalty in Universiti Putra Malaysia (UPM). Therefore, some of the previous study from other researcher to support as the evidence for each variable that have been chosen. Convenience Sampling have been used for sampling technique whereby sample size needed were presented with calculation based on Krejcie and Morgan table. Researcher have conducted the study using the questionnaires and the questionnaire have been distributed to the employee who worked at Universiti Putra Malaysia (UPM). The researcher has used SPSS version 22.0 as the statistic calculation for this research findings. The findings have shown that each factor have positive relationship with employee while work environment is the most factor that contribute to employee loyalty. Furthermore, several recommendations have been proposed in the last part which can help the organization to overcome and improve the employee loyalty in the organization